Can we have our steak and eat it: The impact of breeding for lowered environmental impact on yield and meat quality in sheep - Rowe, S. J.; Hickey, S. M.; Bain, W. E.; Greer, G. J.; Johnson, P. L.; Elmes, S.; Pinares-Patiño, C. S.; Young, E. A.; Dodds, K. G.; Knowler, K.; Pickering, N. K.; Jonker, A.; et al. (Frontiers in Genetics, 2022)
Global agreements in place to reduce methane emissions are a potential threat to food security. Successful but independent breeding strategies for improved production and lower methane are in place. The unanswered question is whether these strategies can be combined, and how they impact one another, physically and economically. The New Zealand economy is largely dependent on pastoral agriculture from grazing ruminants. The sheep industry produces ~20 million lamb carcasses for export each year primarily from grass. Methane emitted from fermentation of forage by grazing ruminants, however, accounts for one third of all New Zealand’s greenhouse gas emissions. Here, we use sheep selection lines bred for divergent methane production and large numbers of their relatives to determine the genetic and phenotypic correlations between enteric methane emissions, carcass yield and meat quality. Primary objectives were to determine whether previously shown physiological differences between methane selection lines (differing by ~12% in methane) result in a negative impact on meat production and quality by measuring close relatives. Results show no negative effects of breeding for lowered methane on meat and carcass quality. Gross methane emissions were highly correlated with live weight and measures of carcass weight and negatively correlated with dressing out percentage and fat yield (GR). Trends were similar but not significant for methane yield (g CH4/kg DMI). Preliminary evidence, to date, shows that breeding for low methane may result in animals with higher lean yield that are economically favourable even before carbon costs and environmental benefits are taken into account. These benefits were seen in animals measured for methane on fixed intakes and require validation on intakes that are allowed to vary.